TREATMENT OF TITTING BEHAVIOR THROUGH GROUP COUNSELING SERVICES BEHAVIORAL APPROACH ASSERTIVE TRAINING TECHNIQUES IN CLASS VII E SMP NEGERI 2 GABUS - Hayu Prima Suryani (Literasi Nusantara, 2022)
This type of research is action research (action research). The form used is guidance and counseling action research (PTBK). This study aims to eradicate student truancy behavior through behavioral group counseling services with assertive training techniques. The research subjects taken were students of class VII E of SMP Negeri 2 Gabus as many as 3 students who often skipped. The results of the first cycle the frequency of truancy decreased by 88.12% and from the second cycle to 100%. Based on the discussion of the results of the writing, it can be concluded that: Group counseling using a behavioral approach to assertive training techniques can reduce truancy behavior for class VII E students of SMP Negeri 2 Gabus. This is found from the attitude of the counselee who is able to be firm when a friend invites him to play truant (the counselee is able to say "no" to things that are considered inconsistent with his feelings). Group counseling with a behavioral approach to assertive training techniques carried out in cycle I to cycle II.